Stabilization of clayey soil for subgrade using rice husk ash (RHA) and sugarcane bagasse ash (SCBA) - Hidalgo, F. (2020)
This document studies the stabilization of the soil used as a subgrade, by adding locally available materials such as rice husk ash (RHA) and sugarcane bagasse ash (SCBA). These aggregates were added to the soil in substitution by weight between 5%, 7.5% and 10%. By adding these, the expansiveness is reduced while the maximum dry density increases, in addition the tendency of CBR is increasing and then tends to decrease proportionally to the addition of the aforementioned aggregates. This indicates a peak in CBR and expandability. The best result obtained from CBR was 33.75% with the 5% replacement mixtures.